2018
DOI: 10.1002/pc.24798
|View full text |Cite
|
Sign up to set email alerts
|

Castor oil‐based polyurethane/silica nanocomposites: Morphology, thermal and mechanical properties

Abstract: As a reinforcing filler, nano‐silica was modified using silane coupling agents (KH560 and KH570). The effects of nano‐silica loadings on the morphology, mechanical and thermal properties of castor oil‐based PU nanocomposites were studied. Scanning electron microscopy demonstrated the relatively homogeneous dispersion of nano‐silica in the PU matrix. After the addition of different nano‐silica, a significant nano‐silica reinforcement effect on castor oil‐based PU matrix was found. The tensile strength and Young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…Analytical-grade acetone, toluene, isopropyl alcohol, acetic acid, hydrochloric acid, and castor oil were all purchased from Shanghai Energy Chemical Co., Ltd. (Shanghai, China). The OH value of castor oil was 160 mg KOH g −1 , which was determined according to the previous report [44]. Isophorone diisocyanate (IPDI) was obtained from Shanghai Aladdin Biochemical Technology Co., Ltd. (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analytical-grade acetone, toluene, isopropyl alcohol, acetic acid, hydrochloric acid, and castor oil were all purchased from Shanghai Energy Chemical Co., Ltd. (Shanghai, China). The OH value of castor oil was 160 mg KOH g −1 , which was determined according to the previous report [44]. Isophorone diisocyanate (IPDI) was obtained from Shanghai Aladdin Biochemical Technology Co., Ltd. (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…The neat PU was synthesized by the reaction of IPDI with castor oil according to our previously described method [44]. The PU/ATT nanocomposites were prepared as follows: the three ATTs (ATT, acid-ATT, and KH560-ATT) were respectively added in dry acetone and the obtained suspension was sonicated for 60 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous works have been reported using castor oil as the replacement of polyols in polyurethane. [3][4][5][6][7] Castor oil, however, has several problems to directly produce a flexible polyurethane foam due to its low reactivity. 8 Also, molecular weight of castor oil is considerably lower than that of the conventional polyol.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al 21 have studied about the morphology, thermal, and mechanical properties of the castor oil‐based polyurethane/silica nanocomposites (PU/SNP). They showed that the SNP surface was modified with 3‐glycidoxypropyltrimethoxysilane and c‐methacryloxy‐propyltrimethoxysilane.…”
Section: Introductionmentioning
confidence: 99%